WHY IS IT IMPORTANT TO INCLUDE SUSTAINABLE AND CLIMATE-SMART PROVISIONS IN REGIONAL TRADE AGREEMENTS OF THE WESTERN BALKAN COUNTRIES - Toshevska trpchevska, Katerina; Kocev, Ljuben; Tonovska, Jasna (Ekonomski fakultet Univerziteta u Istocnom Sarajevu, Pale, 2024)
The goal of this paper is to analyze the incorporation of sustainable and climate-smart provisions in the regional trade agreements signed by the Western Balkans countries. The inclusion of these provisions has been gaining momentum in the international trade agenda as after the Covid-19 Pandemic and the turmoil in the international economy it has become more and more important to take care of the sustainable and climate-smart component in the trade policy. The inclusion of these provisions in trade agreements is essential in achieving sustainable development, pursuing international environmental goals, and fostering environmental cooperation. Western Balkan countries have been active in signing regional trade agreements and for the purposes of this paper we have analyzed the one regional trade agreement CEFTA-2006 signed between the six Western Balkans partners, the bilateral trade agreements signed between the individual Western Balkans partners and the European Union and the bilateral trade agreements signed between these partners with other partners like: Turkey, EFTA, United Kingdom, Ukraine. The analysis has shown that there is an increase in the incorporation of sustainable and climate-related provisions into the trade agreements of Western Balkans countries. The inclusion of such provisions has been particularly evident in trade agreements concluded from 2000 to 2010, with a notable increase in environmental provisions in agreements concluded after 2010. To support the analysis, we applied the software package NVivo 14 used for qualitative analysis and provide results displayed through word clouds, word frequency and word trees. The word “climate” and the word “sustainability” are not among the 1000 most frequently appeared words in the regional trade agreements of the Western Balkans countries. The words “environment” and “environmentally” are mentioned 251 times weighing a total of 0.02% of the agreements. The Nvivo analysis has confirmed the fact that there is still space for improvement and increasing the sustainable and climate-smart provisions in the agreements.
Keywords: regional trade agreements, Western Balkans, sustainable and climate-smart provisions, nVivo